THE INFLUENCE OF TRAINING AND DEVELOPING HUMAN RESOURCES TO EFFECTIVENESS PERFORMANCE OF EMPLOYEES - Gabriyella, Sarah; L.Tobing, Suzanna Josephine; Tampubolon, Emma (Universitas Kristen Indonesia, 2018)
This research is a research using quantitative approach. Quantitative approach or quantitative method can be interpreted as a research method based on positivism philosophy, used to research on a particular population or sample, quantitative or statistical, with the aim to test the hypothesis that has been established. Testing the data hypothesis using a simple Linear Regression technique that shows that there is an influence Training and Developing Human Resources to effectiveness performance of employees at PT Tugu Reasuransi Indonesia. The results showed that 1) Partially, the provision of Training to employees of PT Tugu Reasuransi Indonesia has a strong Relationship with Employee Performance effectiveness, with the Rank Spearman correlation value of 0.668. But the provision of Training does not have a significant effect on the effectiveness of Employee Performance at PT Tugu Reasuransi Indonesia, with t value less than t table (1.289 = 1.467065). 2) Partially, The Development of Human Resources at PT Tugu Reasuransi Indonesia has a very strong relationship with the effectiveness of Employee Performance, with a Rank Spearman correlation value of 0.919. Development of Human Resources also have a significant influence on the effectiveness of employee performance PT Tugu Reasuransi Indonesia, with tvalue greater than ttable (15.009 = 1.467065). 3) Simultaneously, the provision of Training and Development of PT Tugu Reasuransi Indonesia Human Resources has a significant influence on the effectiveness of employee performance, with the calculated Fvalue greater than Ftable (199.950 = 2.39).Key words: The Provision of Training, Developing Human Resources and Performance